Eastern Black Swallowtail: Papilio polyxenes asterius (Stoll) (Insecta: Lepidoptera: Papilionidae) - Donald W. Hall (EDIS)
This document provides an in-depth profile of the eastern black swallowtail butterfly, Papilio polyxenes asterius. It covers its distribution, physical description, life cycle, natural enemies, defenses, host plants, and economic importance. The butterfly is found throughout southern Canada, the eastern and mid-western United States, and northern Mexico. It is admired for its beauty but can occasionally be a pest. The document includes identification keys and discusses management strategies for controlling the butterfly in home gardens. Original publication date November 2011.